1983
DOI: 10.1177/0164027583005003008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Health Services among Disabled Elderly

Abstract: In order to facilitate program planning for the chronically ill, it is essential to understand their propensity to use health and social services. This study has systematically examined the use of ambulatory services among the noninstitutionalized elderly (N = 772) who reported with one or more activity-limiting chronic conditions in a statewide survey of older Virginians in 1979. The determinants of differential use of physician services are investigated. The independent variables included in the analysis are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 13 publications
2
35
1
1
Order By: Relevance
“…We based inclusion criteria on factors associated with home-care use (Branch et al, 1988;Choi, 1994;Soldo, 1985;Wan & Arling, 1983;Wolinsky & Johnson, 1992). The inclusion criteria were as follows: (a) being 80 years of age or older, (b) living alone at home, (c) having been widowed for at least 1 year, (d) having children, and (e) living in the town where one had lived when married.…”
Section: Samplingmentioning
confidence: 99%
“…We based inclusion criteria on factors associated with home-care use (Branch et al, 1988;Choi, 1994;Soldo, 1985;Wan & Arling, 1983;Wolinsky & Johnson, 1992). The inclusion criteria were as follows: (a) being 80 years of age or older, (b) living alone at home, (c) having been widowed for at least 1 year, (d) having children, and (e) living in the town where one had lived when married.…”
Section: Samplingmentioning
confidence: 99%
“…3 Prior studies have documented that people with disabilities face disparities in health and healthcare as compared to people without disabilities. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Though some studies assessing healthcare disparities for adults with developmental disabilities have included participants on the autism spectrum, with the exception of one small study using administrative data, 21 they do not report results separately for autistic participants. Most studies also primarily include participants with intellectual disabilities, and may not be generalizable to the full range of individuals now recognized as on the autism spectrum, a majority of whom do not have an intellectual disability.…”
mentioning
confidence: 99%
“…This, according to Aday and associates (1980), is to be ex pected. However, some researchers have expressed concern about the inability of the model to explain a large variance in service use (Wan and Arling 1983;Wolinsky 1978;Mechanic 1979). The test of this component by Fosu (1989) along the lines being pro posed in this study showed that, by examining the use of health services by children and mothers separately, the variance explained by the model improved considerably.…”
Section: Conceptual Modelmentioning
confidence: 68%